2015
DOI: 10.1186/s12917-015-0561-z
|View full text |Cite
|
Sign up to set email alerts
|

Temperatures of storage areas in large animal veterinary practice vehicles in the summer and comparison with drug manufacturers’ storage recommendations

Abstract: BackgroundLarge animal veterinarians carry drugs in their practice vehicles in storage areas that are not typically refrigerated. The most common upper limits of manufacturers’ storage temperatures for United States (U.S.)-approved non-refrigerated drugs are 25 or 30 °C. Because ambient temperatures in many locations in the U.S. exceed these temperatures during the summer, we measured storage area temperatures over 4 months in the summer of 2013 to evaluate the extent to which labeled storage temperatures are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Most drugs have a storage temperature requirement of less than that and is likely to reduce drug potency. In the United States (US), the upper limits of manufacturers' storage temperatures for approved non-refrigerated drugs are between 25 and 30 °C (Ondrak et al, 2015). It may therefore be worthwhile to carry out studies to determine the effect of storage on veterinary drug potency.…”
Section: Discussionmentioning
confidence: 99%
“…Most drugs have a storage temperature requirement of less than that and is likely to reduce drug potency. In the United States (US), the upper limits of manufacturers' storage temperatures for approved non-refrigerated drugs are between 25 and 30 °C (Ondrak et al, 2015). It may therefore be worthwhile to carry out studies to determine the effect of storage on veterinary drug potency.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccines may be delivered by practice members (eg, vets going out to farm visits) or picked up from a practice by the clients themselves. Veterinary vehicles and veterinary medicine storage compartments are routinely reported to exceed the temperature storage requirements for most veterinary medicines (Ondrak and others 2015), so providing specific cool storage such as a cool box for the transportation of vaccines, both for vets and clients, would be a cost‐effective way of ensuring that the cold chain is maintained until vaccines reach a farm.…”
Section: Storagementioning
confidence: 99%
“…Rees and others (2019) found that expired veterinary medicines were stored on 25 of the 27 farms in their study. While some efficacy is assumed after the expiry date of unopened veterinary medicines, large‐scale studies and information on specific products are not widely available (Ondrak and others 2015). As it is difficult to assess how the expired products stored on farms are used, this warrants further investigation both from vets in practice as suppliers of veterinary medicines (ie, how often are products being used after the expiry date and why?)…”
Section: Usage and Handlingmentioning
confidence: 99%
“…Beside bags [ 13 ], although boxes are used to transport and store temperature-sensitive drugs in veterinary vehicles [ 2 , 3 , 14 ], it often remains unclear whether they are appropriate for this purpose. However, to the knowledge of the authors, no systematic investigations on the suitability or practicability of passive storage boxes for drug transport in vehicles have been published so far.…”
Section: Introductionmentioning
confidence: 99%
“…Both exceedance of the upper temperature limit and a shortfall of the temperature to below the lower limit (e.g., freezing) must be considered. The discrepancy between the thermal needs and requirements to store drugs and the realities was shown by Haberleitner et al [ 2 ] and Ondrak et al [ 14 ] for veterinary vehicles.…”
Section: Introductionmentioning
confidence: 99%